Euro Area Export Performance and Competitiveness - Turunen, Jarkko (IMF Working Papers; Working Paper ;, 2011)
Concerns about export growth within the euro area peripheral countries due to a lack of competitiveness within the euro area are a key policy issue. Our analysis suggests that: (i) Long-term price elasticities for intra-euro area exports are at least double those for extra-euro area exports, so traditional real effective exchange rate indexes may overstate the effectiveness of euro depreciation in restoring exports growth in the euro area periphery and; (ii) There are surprisingly wide divergences across alternative relative price measures and even when relative price data suggest a steady loss in intra- (and extra-) euro area competitiveness, the pace of deterioration depends on the measure of relative prices used.